Pengukuran Trend Analysis Dalam Menilai Performance Management Dan Mempertahankan Business Continuity Management - Anggit Dyah Kusumastuti; Annisa Indah Mutiasari; Destina Paningrum; Rusnandari Retno Cahyani (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
The covid-19 pandemic has affected the industrial sector which has an impact on the cessation of the wheels of business and must stop operating. The results of the 2020 Central Statistics Agency (BPS) survey noted that 82,85% of companies were affected by the covid-19 virus. Based on the sector, accommodation and beverage/food business experienced the most decline in income, which was 92,47%. The purpose of this study is to determine the percentage increase or decrease in account items in statement of financial position in the base year 2019 and the comparison years 2020 and 2021in manufacturing companies that listed on the Indonesia Stock Exchange. Based on data analysis, it is concluded that the company’s financial performance from the 2019-2021 periode has increased and decreased, which can be seen from the comparison per two years on the balance sheetbased on trend analysis. Increases and decreases in performance have no significant effect because the company is still able to run and operate. From the result of the analysis of financial statements using the trend method, it can be concluded that the ICBP company has the best performance seen in the accounts on the balance sheet which has increased compared to other companies.